Knowledge-based system for rainfed natu tobacco (Nicotiana tabacum) germplasam - Ravisankar, H; Sarala, K; Murthy, T G K (The Indian Journal of Agricultural Sciences, 2012)
Tobacco (Nicotiana tabacum) is a commercial crop in many countries. Most of them are maintaining large number of germplasm collections without computer databases. Accessing the large amounts of plant genetic resource data requires the development of germplasm databases. Tobacco germplasm are of different ‘types’, with large numbers of accessions in each type. Among the different tobacco types grown in India, rainfed natu tobacco is an indigenous type mainly used for domestic consumption. Based on the data available on various parameters of rainfed natu tobacco accessions, a knowledge-based system for rainfed natu tobacco germplasm was developed with user-friendly menus using RDBMS technology. This software allows the users to store, update and retrieve the germplasm data of all tobacco types on various parameters and acts as a decision-making tool. This database can be kept in the web server for global accessing.